Existence of radial solutions for indefinite semilinear elliptic equations - Calahorrano, Marco (2020)
We study the existence of radial solutions of indefinite semilinear elliptic equations in the unit ball in Rn (n>=3) with Dirichlet boundary conditions, whose nonlinear term has the form lamda.m(|x|)f(u) where m(|.|) is radially symmetric, discontinuous and changes sign. This study is realized using variational tecniques and especially the Ambrosetti-Rabinowitz’s “Mountain Pass Lemma”.